2001
DOI: 10.1080/028418601750288262
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological Hypoxia, Oxygen Tension, Interstitial Fluid Pressure and Relative Viable Tumour Area in Two Human Squamous Cell Carcinomas in Nude Mice During Fractionated Radiotherapy

Abstract: Very little is known about the correlation between the radiobiological hypoxic fraction (rHF) and other measures of tumour oxygenation during fractionated irradiation. In the present study the rHF is determined in untreated human FaDu and GL squamous cell carcinoma in nude mice and in tumours irradiated with 10 fractions in 2 weeks and 20 fractions in 4 weeks, using tumour control as the experimental endpoint. The results were compared with measurements of the pO2, the interstitial fluid pressure (IFP) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…For example, in SAS pHV transiently increased after five fractions and returned to baseline level later during the course of treatment. This intertumoral heterogeneity in the kinetics of oxygenation during fractionated irradiation is in line with the findings of experimental and clinical studies (11,(18)(19)(20)(21)(23)(24)(25). In our study, improved tumor oxygenation shown by the decrease in pimonidazole hypoxia indicates that effective reoxygenation occurred during treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, in SAS pHV transiently increased after five fractions and returned to baseline level later during the course of treatment. This intertumoral heterogeneity in the kinetics of oxygenation during fractionated irradiation is in line with the findings of experimental and clinical studies (11,(18)(19)(20)(21)(23)(24)(25). In our study, improved tumor oxygenation shown by the decrease in pimonidazole hypoxia indicates that effective reoxygenation occurred during treatment.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicate a limited prognostic value of these parameters when determined before fractionated irradiation. Experimental and clinical studies demonstrated that after single-dose and fractionated irradiation parameters of the tumor microenvironment, such as hypoxic fraction, vasculature, and perfusion, might change and have an impact on radiation response (11,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). To explore the prognostic value of the microenvironmental parameters during fractionated irradiation, we selected six hSCC from the previously studied panel with different radiation sensitivity and measured hypoxia, perfusion and vasculature before and during fractionated irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Baumann et al (1994), radiotherapy (top up) in the present study was administered under acutely hypoxic conditions. Under these conditions, However, according to the data of Baumann et al (2001), the hypoxic fraction of surviving clonogenic tumour cells at the end of the fractionated radiotherapy is close to 100% in FaDu dd tumours on nude mice. These data gave indirect evidence that top up irradiations under ambient conditions might have given identical results and that our results are entirely consistent with results of Baumann et al (1994Baumann et al ( , 2001.…”
Section: Discussionmentioning
confidence: 87%
“…Under these conditions, However, according to the data of Baumann et al (2001), the hypoxic fraction of surviving clonogenic tumour cells at the end of the fractionated radiotherapy is close to 100% in FaDu dd tumours on nude mice. These data gave indirect evidence that top up irradiations under ambient conditions might have given identical results and that our results are entirely consistent with results of Baumann et al (1994Baumann et al ( , 2001. The dose needed to counteract tumour cell repopulation can be calculated from the CHART (Dische et al, 1997) and V-CHART (Dobrowsky and Naude, 2000) clinical trials.…”
Section: Discussionmentioning
confidence: 87%
“…In a study of the physiology of pharyngeal tumors (approved by the ethics commission of the University Hospital “Carl Gustav Carus” at the Technical University of Dresden), ( 5 ) the invasively measured extracellular oxygen partial pressure in the tumor tissue was determined. Its polarographical measurement is the gold standard for the description of tumor oxygenation (many other methods, such as oxygen tension, interstitial fluid pressure, and vital tumor fraction, do not correlate to the measured data by means of pO2 probes ( 6 ) ). Glucose metabolism activity was described by means of positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%